Identification and antimicrobial susceptibility of enterococcal species isolated from cats exposed to different antibiotics - Mohd Amin, Nor Azimah (2016)
Enterococci are part of normal microbial flora in the gastrointestinal tract of human and animals. They have emerged to pose a significant public health concern through its emergence of being opportunistic in causing nosocomial infections as well as acquiring high level of resistance to many antimicrobial agents. Vancomycin-resistant enterococci (VRE) appearance has caused serious problems in human and veterinary medicine. The objectives of this study were to isolate and identify enterococci in cats exposed to different antibiotics and to determine its antimicrobial susceptibility pattern. Thirty (30) rectal swabs of cats were collected from a veterinary clinic and processed for isolation and identification of enterococci by inoculating the samples onto blood agar and followed by biochemical tests. The isolates were then subjected to antimicrobial susceptibility test (AST) to six antibiotics namely amoxicillin, amoxicillin and clavulanic acid, enrofloxacin, marbofloxacin, doxycycline, and vancomycin. Six rectal swab samples were positive for enterococci. The enterococci isolates were consists of E. faecalis (3 isolates), E. durans (3 isolates) and Enterococcus sp.(1 isolate). None of the isolates were resistant to all six antibiotics tested. Enterococcus sp. isolate was resistant to five antibiotics (amoxicillin, amoxicillin and clavulanic acid, enrofloxacin, marbofloxacin, and doxycycline). One isolates of E. faecalis was resistant to four antibiotics (amoxicillin and clavulanic acid, enrofloxacin, marbofloxacin, and doxycycline). One E. faecalisand one E. durans were resistant to three antibiotics (amoxicillin and clavulanic acid, enrofloxacin, and marbofloxacin). Two E. durans and one E. faecalis were resistant to two antibiotics (enrofloxacin and marbofloxacin). All enterococci isolates were resistant to enrofloxacin and marbofloxacin whilst vancomycin was the antibiotic that all the isolates were sensitive to. Two multi drug resistant (MDR) enterococci and two extensively drug resistant (XDR) enterococci were detected in this present study.